INDIKASI FENOMENA STRUKTUR GEOLOGI BAWAH PERMUKAAN DAERAH RENCANA TAPAK PEMBANGKIT LISTRIK TENAGA NUKLIR GUNUNG API GENUK DAN SEKITARNYA, JEPARA, JAWA TENGAH - Saultan Panjaitan; Subagio Subagio (Jurnal Geologi dan Sumberdaya Mineral, 2009)
Generally, gravity anomaly pattern in research area is devided into two groups, high anomaly with the value ranges from 37 mgal to 43 mgal, and low anomaly, varies from 10 mgal to 37 mgal. The high anomaly group might be caused by the existing volcanic Quartenary rocks, and the low anomaly group indicates a sedimentary basin. Based on the result of 3 quantitative analysis, the high anomaly group reflects the existing volcanic Quartenary rocks with density 2.8 gr/cm relatively higher than surrounding. Analysis also shows in the site plan of Ujung Lemahabang the predicted faults are not encountered. The area in radius 5 km from research area, predicted the capable fault not exist in radius 25 km, found two faults ofshore and three faults in western part of investigation area.Â Keywords : Lemahabang, gravity anomaly, sedimentary basin arc fault